MANAJEMEN PONDOK PESANTREN AL-MADANI DALAM PENGEMBANGAN UMMAT DI DESA MAMBEN LAUK LENGKOK AL-KHAIRAT LOMBOK TIMUR - Rahmat Hidayat (UIN Mataram, 2023)
This paper aims to investigate the role and position of the al-Madani Islamic boarding school, one of the Islamic boarding schools that has a positive trend in society through efforts to develop an understanding of community religion, especially in Mamben Lauk Village, Lengkok Al-Khairat, East Lombok. In this paper, the main focus of discussion is emphasized on the personal religious management programs that are offered and run. Several important issues that will be answered in this research are, what kind of maps are the religious programs offered by the Al-Madani Islamic boarding school?, Second, what is the management of religious programs at the Al-Madani Islamic boarding school? In general, the data in this paper were obtained through field research using a quantitative approach. Meanwhile, related information was obtained through in-depth interviews, observation, and documentation. The results of this study indicate that the religious programs of Al-Madani Islamic Boarding School have been very well planned and arranged in accordance with the three principles of management science, namely planning, organizing, actuating, controlling.